Advances in the study of the relationship between Alzheimer's disease and the gastrointestinal microbiome. Issue 4 (8th September 2022) - Li, Xin‐Yan; Qin, Hao‐Yue; Li, Ting‐Ting
Abstract: There are many trillions of bacteria in the gastrointestinal microbiome (GM). Their ecological dysregulation can contribute to the development of certain neurodegenerative diseases, including Alzheimer's disease (AD). AD is common dementia and its incidence is increasing year by year. However, the relationship between GM and AD is unclear. Therefore, this review discusses the relationship between GM and AD, elaborates on the possible factors that can affect this relationship through the inflammation of the brain induced by blood−brain damage and accumulation of amyloid deposit, and proposes feasible ways to treat AD through GM‐related substances, such as probiotics, Mega‐3, and gut hormones, including their shortcomings as well. Abstract : Alzheimer's disease (AD) is a common degenerative disease faced by humans and its prevalence has been increasing recently, but there is no exact cause and mechanism of its development. This review discusses how and why abnormalities in the gastrointestinal biome may contribute to AD and the treatments associated with it.